Electromagnetics in active parts of converter transformers - Ketola, Jaakko (My University, 2019)
Transformers used in power electronics applications are subjected to harmonics and increased dielectric stresses due to non-linear electric loads. Therefore, regular distribution transformers are not viable, but specially designed converter transformers are required. This work is a part of a research and development project at the Transformers unit of ABB oy in Vaasa, aimed at establishing technical standards and design guidelines for special converter transformers. The first subject of this thesis is to study a new prototype intermediate yoke used in converter transformers. Intermediate yokes enable phase displaced active parts to be constructed on a single core by absorbing the difference of the magnetic fluxes. A new intermediate yoke prototype is presented as a solution to reduce production time. The feasibility of this new solution is verified by modelling and simulating a prototype that is also constructed and tested in practice. In addition, no-load loss calculation for three-phase converter transformers equipped with intermediate yokes is reviewed to improve calculation accuracy. The second subject is to study the effects of reduced radial distances on capacitive coupling of windings. The electrostatic grounding shield works as a filter between primary and secondary windings and suppresses transfer of harmonic currents by reducing capacitive coupling between the windings. It was suspected that losses in the shield could raise to critical levels and overheat the shield if radial distance is reduced. The issue is studied with 2D FEM capacitance simulations under different conditions, FRA and circuit simulations. Theoretical findings are in accordance with the simulation and test results for the intermediate yoke. Feasibility is proven, recommendations for guidelines are established, and a reform proposal for no-load loss calculation is presented. Losses due to capacitive coupling in the grounding shield are found to be insignificant, even with reduced radial distances.
Keywords: converter transformer; no-load losses; harmonics; intermediate yoke; electrostatic ground shield; FEM; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|